Tributyrin (CoreBiome®) enhances butyrate levels and modulates the gut microbiota, barrier function, and immune response in vitro - Duysburgh, Cindy; Verstrepen, Lynn; Van Meulebroek, Lieven; Marzorati, Massimo (Frontiers in Nutrition, 2025)
Background/objectivesOral butyrate is unstable during upper gastrointestinal tract (GIT) transit and very little reaches the colon. Tributyrin, a butyrate precursor, resists gastric acid and is converted to butyrate by pancreatic lipases. This study aimed to quantify tributyrin stability during upper GIT passage and to uncover the effects of tributyrin supplementation on the human gut microbiome and cellular responses.MethodsIn vitro upper GIT simulations were used to evaluate the stability of a capsule and softgel formulation of tributyrin (CoreBiome®). The effects of tributyrin supplementation on the human gut microbiome and cellular responses were evaluated using the Simulator of the Human Intestinal Microbial Environment (SHIME®) model and Caco-2/THP1 co-cultures.ResultsThe upper GIT simulations showed that 40.9 and 48.7% of the tributyrin dose administered via the capsule or softgel, respectively, was hydrolyzed to butyrate in the small intestine; 59.1 and 51.3% remained stable and was available to enter the colon. Using the SHIME® model, it was shown that 3 weeks of daily tributyrin supplementation increased butyrate levels and enhanced the abundance of several bacterial species, including Bifidobacterium spp. and Akkermansia mucinophila. Metabolic impacts on the gut microbiome were also observed. Assessment of cellular responses revealed that tributyrin fermentation had a protective effect on the intestinal barrier and exerted immunomodulatory properties.ConclusionEnhanced butyrate concentrations and beneficial impacts on the gut microbial community composition were observed in an in vitro simulation of the human intestinal environment, suggesting that tributyrin could be considered as a solid alternative to butyrate supplementation.